Kinetic and kinematic differences between first and second landings of a drop vertical jump task: Implications for injury risk assessments? - Batesa, N. A.; Ford, K. R.; Myer, G. D.; Hewett, T. E. (Clinical Biomechanics, 2013)
Though the first landing of drop vertical jump task is commonly used to assess biomechanical performance measures that are associated with anterior cruciate ligament injury risk in athletes, the implications of the second landing in this task have largely been ignored. We examined the first and second landings of a drop vertical jump for differences in kinetic and kinematic behaviors at the hip and knee.